Automated essay grading system / Cheong Tau Pau - Cheong, Tau Pau (2005)
The aim of this project is build an automated essay grading system which can aid in the current manual essay grading process. The core objective of the project is to develop the system for grading essay written in Malay language for the History subject. The secondary objective is to compare the efficiency of the nearest neighbor algorithm and the vector space model. Reviews on system and algorithm are done to obtain more information about developing the system. Automated essay grading system is a web based system that used by the teachers and students. The system could aid the teacher in assessing the essay submitted by the student in electronic form. The students could use the system to practice their essay submitted. The student can only view their own results where the teachers could view all the students result. The system should be available online 24 hours a day throughout the year except for unexpected reasons. The Waterfall Methodology with prototyping was chosen to develop the automated essay grading system. The web based application will be served using Microsoft IIS and it will be developed using ASP.Net with VB.Net and Javascript as backend Microsoft SQL Server 2000 will be use as the database system.